Methamphetamine addiction : towards a prevention strategy in a ministerial approach to substance abuse during mid-adolescence within the Lavender Hill setting - M'Buka, Attlee Charles (Stellenbosch : Stellenbosch University, 2014)
Thesis (MTh)--Stellenbosch University, 2014.